The effectiveness of vocational school performance measurement model based on balance scorecard - Desmi Irianti; Sufyarma Marsidin; Kasman Rukun; Jalius Jama (International Conferences on Educational, Social Sciences and Technology)
The current models of vocational school performance measurement refer to the eight National Standards of Education. They are accreditation and school seif-evaluation models, and the models are not effective yet, as they did not measure school performance from all aspects of the school life. Therefore, to measure school performance comprehensively and effectively, by using A Model of Vocational School Performance Measurement based on Balance Scorecard. The type of the research is development research. The development model procedure followed the model from Borg and Gall (2008: 570). Data collection used instrument replenishment to all school stakeholders. The collected data then were analyzed using scoring on each measurement indicator. The results obtained based on the stages of product development trial to 46 respondents. The result of study showed that the vocational school performance measurement model is very effective. The Effectiveness of model wastaken by filling questionnaires that contains of 13 statements and distributed to 46 respondents of four SMKs in Pesisir Selatan Regency. The effectiveness level of the model book is 91.24%, while the format book is 94.31%. It means that the books of the Vocational School Performance Measurement Model based on Balance Scorecard are very effective to measure the performance of vocational high schools.